0832 Physical Exercise Improves Sleep and Muscle Function in Sarcopenic Patients: A Randomized Controlled Trial. (27th May 2020) - De Sá Souza, H; Piovezan, R D; Chagas Miranda, R E; Silva, B M; Tufik, S; Poyares, D; D'Almeida, V
Abstract: Introduction: Sarcopenia is a multifactorial condition that, like sleep debt, affects the elderly and is related to metabolic, endocrine, inflammatory alterations and risk to mortality. Resistance training (RT), in turn, can improve both factors. Aim: investigate the effects of 12-week RT on sleep and muscle function in the sarcopenic elderly. Methods: 28 sarcopenic elderly were equally distributed in 2 groups at random: CTL: who participated in weekly lifestyle change lectures or; RT: who did the progressive load RT. Sleep was assessed by polysomnography, actigraphy and questionnaires. Isokinetic and isometric of peak torque (PT) of skeletal muscle, anabolic and catabolic hormones, pro and anti-inflammatory cytokines concentrations were also evaluated. For intention to treat analysis (Δ) the generalized linear/non-linear for absolute variables or Wilcoxon rank-sum (Mann-Whitney) test. Data are expressed as mean±standard deviation or median, minimum and maximum values and difference witch p<0.05. Results: The RT reduced the time to sleep onset (16.09±15.21) compared to CTL (29.98±22.57) group after the intervention. The Δ shows that RT had more N3 sleep (median:0.90, min:-13.40, max: 25.00) than CTL (median:-3.35, min:-15.20, max:19.10). The RT increases TTS (median:57.55, min:-204.75, max:220.91 vs median:-9.63, min:-120.98, max:185.57) and improved self-reported sleep quality (median: -1.50, min: -9.00, max: 4.00 vs median: 0.50, min: -3.00, max: 6.00) and sleep efficiency (median: 9.50, min: -15.00, max: 34.00 vs 0.00, min: -28.00, max: 18.00). For all muscle function parameters (extension and flexion knee in isokinetic or isometric PT) RT had higher values compared to CTL group after 12 weeks of intervention (p<0.05). IL-1ra concentrations were higher in RT (median: 0.04, min: -0.02, max: 0.36) vs CTL (median:-0.01, min:-0.12, max:0.07). Conclusion: Progressive load resistance training improves sleep parameters associated to muscle recovery in elderly people with sarcopenia, along with positive changes in physical performance. Support: Associação Fundo de Incentivo à Pesquisa (AFIP), Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) and Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP).